LAUNCH PARAMETERS OF AN ICE PAYLOAD TRAVELING VIA LUNAR ELECTROMAGNETIC LAUNCHER TO THE LUNAR GATEWAY - Beemer, Heidi D. (Monterey, CA; Naval Postgraduate School, 2021)
This paper investigated one possible solution for procuring propellent needed for future space exploration missions. This study examined the feasibility of using an electromagnetic launcher (EML) to transport raw materials used in propellent production from the lunar south pole to NASA’s Lunar Gateway. This proposed space station, located in a lunar near-rectilinear halo orbit (NRHO), is a critical part of NASA’s Artemis program. Cheaply and efficiently sourcing lunar hydrogen from surface ice to the station would benefit the program’s success and future exploration of the solar system. This research investigated the launch requirements for a lunar EML payload. AGI Inc.’s Systems Tool Kit (STK) was used to calculate the required launch azimuth, elevation, magnitude, epoch, and trip duration needed to intercept the Gateway. The model evaluated the payload and the Gateway’s radial, cross-track, and in-track positions and rates to determine their relative positions and velocities at rendezvous. Conclusions from this research demonstrated that it is feasible to conduct a single launch from the lunar south pole and target any point along the Gateway’s orbit with variable launch conditions. Evidence supporting our hypothesis is presented, showing it may not be possible to match the space station’s state vector at rendezvous. The payload will require an additional thrust capability, suggestions for which were also explored in this paper. Approved for public release. distribution is unlimited Captain, United States Army